2022
DOI: 10.3389/fpsyg.2022.1030059
|View full text |Cite
|
Sign up to set email alerts
|

Cultural factors and senior tourism: Evidence from the Chinese context

Abstract: Recently, numerous studies have focused on tourism among the older population. Of them, most reported on status analysis, tourism motivation, and tourism model, to name a few; however, there was a lack of comprehensive synthesis and analysis of the motivation, influencing factors, policy impact, and other factors of older tourism. Thus, this study conducted various keyword searches among both English and Chinese publications. We found that older population’s tourism is affected by various factors, such as trav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…Regarding economic drivers, this study found that an increasing disposable income among urban retirees is a demand driver for RSHTUE development, which is consistent with Hsu et al [58] and Tuo et al [59]. The current study found low consumer prices in destinations to be a demand driver for RSHTUE development, consistent with Tuo et al [59], Cheng et al [64], and Singh [71]. The present study found that additional investment in hospitality facilities by investors and villagers is a supply driver of RSHTUE development, consistent with Pestana et al [61] and Wong and Musa [66].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Regarding economic drivers, this study found that an increasing disposable income among urban retirees is a demand driver for RSHTUE development, which is consistent with Hsu et al [58] and Tuo et al [59]. The current study found low consumer prices in destinations to be a demand driver for RSHTUE development, consistent with Tuo et al [59], Cheng et al [64], and Singh [71]. The present study found that additional investment in hospitality facilities by investors and villagers is a supply driver of RSHTUE development, consistent with Pestana et al [61] and Wong and Musa [66].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding economic drivers, this study found that an increasing disposable income among urban retirees is a demand driver for RSHTUE development, which is consistent with Hsu et al [58] and Tuo et al [59]. The current study found low consumer prices in destinations to be a demand driver for RSHTUE development, consistent with Tuo et al [59], Cheng et al [64], and Singh [71].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As a result of their life and professional experience, they give importance to these segments of the development of congress tourism. The older generation observe tourism differently than the younger one and for them tourism represents a component that can inevitably improve the quality of life (Tuo et al, 2022;Wang & Luo, 2014). The situation is similar regarding the following factors: Community-centered economy, Ensuring visitor satisfaction and Maximizing community participation, where the perception of the importance of these segments of tourism increases with age.…”
Section: Anovamentioning
confidence: 99%